Impella CP implantation during cardiopulmonary resuscitation for cardiac arrest: a multicenter experience. (2nd May 2022) - Panagides, V; Vase, H; Shah, S; Basir, MB; Mancini, J; Kamran, H; Batra, S; Laine, M; Eiskjaer, H; Karami, K; Paganelli, F; Henriques, JP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Abstract: Background: Impella CP is a left ventricular pump which may serve as a circulatory support during cardiopulmonary resuscitation (CPR) for cardiac arrest (CA). Nevertheless, the survival rate and factors associated with survival in patients undergoing Impella insertion during CPR for CA are unknown. Methods: We performed a retrospective multicenter international registry of patients undergoing Impella insertion during on-going CPR for in- or out-of-hospital CA. We recorded immediate and 30-day survival with and without neurologic impairment using the cerebral performance category score and evaluated the factors associated with survival. Results: Thirty-five patients had an Impella CP implanted during CPR for CA. Refractory ventricular arrhythmias were the most frequent initial rhythm (65.7%). In total, 65.7% of patients immediately survived. At 30 days, 45.7% of patients were still alive. The 30-day survival rate without neurological impairment was 37.1%. In univariate analysis, survival was associated with both an age < 75 years and a time from arrest to CPR ≤ 5 min (p = 0.035 and p = 0.008, respectively). Conclusions: In our multicenter registry, Impella CP insertion during ongoing CPR for CA was associated with a 37.1% rate of 30-day survival without neurological impairment. The factors associated with survival were a young age and a time from arrest to CPR ≤ 5 min.